1998
DOI: 10.1086/316190
|View full text |Cite
|
Sign up to set email alerts
|

CLOUDY 90: Numerical Simulation of Plasmas and Their Spectra

Abstract: CLOUDY is a large-scale spectral synthesis code designed to simulate fully physical conditions within an astronomical plasma and then predict the emitted spectrum. Here we describe version 90 (C90) of the code, paying particular attention to changes in the atomic database and numerical methods that have affected predictions since the last publicly available version, C84. The computational methods and uncertainties are outlined together with the direction future development will take. The code is freely availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
2,404
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,426 publications
(2,443 citation statements)
references
References 164 publications
14
2,404
0
7
Order By: Relevance
“…Our theoretical results, obtained for ions in both the ground and metastable states, have been compared with high-resolution experimental measurements and with other theoretical methods. They should be suitable for incorporation into astrophysical modeling codes such as CLOUDY [57,58], XSTAR [20], and AtomDB [59] used to numerically simulate the thermal and ionization structures of ionized astrophysical nebulae.…”
Section: Discussionmentioning
confidence: 99%
“…Our theoretical results, obtained for ions in both the ground and metastable states, have been compared with high-resolution experimental measurements and with other theoretical methods. They should be suitable for incorporation into astrophysical modeling codes such as CLOUDY [57,58], XSTAR [20], and AtomDB [59] used to numerically simulate the thermal and ionization structures of ionized astrophysical nebulae.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the contribution from a photo-ionized plasma near an INS, as mentioned above, we have used the widespread photoionization code CLOUDY (calculations were performed with version 07.02.02 of Cloudy, as described by Ferland et al 1998). Despite the restrictions (luminosity of the ionizing source, ionization parameter, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Noting that He star disruptions would be exceedingly rare, Guillochon et al (2014) instead argued for the disruption of a normal main-sequence star but with the hydrogen line emission suppressed by photoionization effects (e.g., Korista & Goad 2004). Gaskell & Rojas Lobos (2014) performed new calculations using the photoionization code CLOUDY (Ferland et al 1998(Ferland et al , 2013 and showed that, if the lines are optically thick, radiation transport effects may reduce the hydrogen emission line strength. However, a separate CLOUDY parameter study performed by Strubbe & Murray (2015) disputed this interpretation, concluding that, for the conditions relevant to TDEs, hydrogen lines would not be suppressed enough to be consistent with the observations of PS1-10jh.…”
Section: Introductionmentioning
confidence: 99%